Biological Activity and Cytotoxic Effect of Iraqi Wild Mentha arvnesis Total Flavonoid - Yaseen Mohammed Hasan, Zainab; M.F. Al-Halbosiy, Mohammad; Al-Nauimi, Ebtehal (International Journal of Engineering and Technology, 2018)
The major source of flavors and fragrances raw material is Mentha arvensis. The flavonoids were extracted from the leaves of the mature Mentha arvensis by reflex, and then the flavonoids of the extract were detected qualitatively with TLC technique. The plant was found to be rich in flavonoids, especially Rutin, Quercetin, Kaempferol, luteolin and others. This study conducted to assess the biological and cytotoxic effect of this purified total flavonoid on cell lines (L20B and MCF-7) and Leishmania (Leishmania tropica and Leishmania donvani). The extract inhibited the growth of cell line to reach a maximum growth inhibition rate 64.5 % at the concentration (5 mg/ml) for L20B and 52.4% for MCF-7 at the concentration (10 mg/ml) in comparison with negative control. Also the concentration 5mg/ml of plant extract caused an inhibition in the growth of both type of Leishmania to reach to 30.7% for Leishmania tropica and 50.2 % for Leishmania donovani.Â Â